Controller tuning [electronic resource]. (Herndon, Viginia ITC Learning Corporation, 1996)
Summary: This program introduces the Ultimate Method, the Reaction Curve Method, and the Trial and Error Method of controller tuning. It examines the steps needed to tune a controller and allows the student to apply these steps using the three methods o
System requirements: Windows: 486/66 with 256K cache ; 16 MB RAM
Keywords: Automatic control; Control theory